2013
DOI: 10.1177/0731684413475911
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical behavior of cotton/vinyl ester composites: Effects of some flame retardants and fiber treatment

Abstract: Natural fibers are low-cost fibers with low density and high specific properties. These fibers are biodegradable and non-abrasive. The natural fiber composites offer unique properties comparable to those of conventional synthetic fiber composites. However, development of these composites is often hampered by weak compatibility between fibers and polymer matrix and poor thermal resistance, which often reduce their performance. This paper reports thermal properties and flammability of cotton/vinyl ester composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 22 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…There are three stages of weight loss in the TGA plot, indicating that the decomposition of the BKNO 3 sample initiated at around 300, 410, and 500 °C. The first two stages are attributed to the weak stability of ester groups 35 in laminac and the weight losses were 3.3% and 2.3%, respectively. The polymer binder was perfectly decomposed at 410 °C with a total weight loss of 5.6%.…”
Section: Resultsmentioning
confidence: 99%
“…There are three stages of weight loss in the TGA plot, indicating that the decomposition of the BKNO 3 sample initiated at around 300, 410, and 500 °C. The first two stages are attributed to the weak stability of ester groups 35 in laminac and the weight losses were 3.3% and 2.3%, respectively. The polymer binder was perfectly decomposed at 410 °C with a total weight loss of 5.6%.…”
Section: Resultsmentioning
confidence: 99%
“…The only difference is that M in Figure 8b The 2D simulation data τ sim and M are shown with the experimental data τ exp of untreated cotton/vinyl ester composites reported in Ref. [53] in Figure 9a-d. In the experimental data for τ exp (×) in Figure 9a,c, no upturn is observed [54].…”
Section: It Is Confirmed Frommentioning
confidence: 83%
“…Cellulose fabricated VER composites showed a gradual increase in water uptake, tensile modulus, and flexural strength with an increase in cellulose fiber volume fraction in composites (Alhuthali and Low 2013a). The thermal and mechanical behaviors of alkali-treated and -untreated cotton-fiberreinforced VE composites have also been reported by Shahedefar and Rezadoust (2013). It was observed that the use of alkali-treated cotton fiber to reinforce VER improved the tensile strength and elongation-at-break of composites by 5% and 25%, respectively, as compared with that of untreated cotton fiber composites due to increased surface roughness by the removal of wax and oil from the surface of the fibers.…”
Section: Vers As Matrix For Composite Materialsmentioning
confidence: 86%